Glycolipids as Potential Energy Molecules during Starvation in Climbing Perch, Anabas testudineus (Bloch) - Padmavathi Godavarthy; Y. Sunila Kumari (International Journal of Zoology)
Glycolipids are membrane lipids which act as cellular markers and also provide energy for the cells. The present study is an attempt to understand whether glycolipids can act as energy sources during fasting. To achieve this, we selected and subjected Anabas testudineus to short-term (15 days) and long-term (60 days) laboratory starvation. We estimated glycolipids biochemically using a standard protocol in six different tissues. Results showed a selective decline in glycolipid concentration in certain tissues, and also an increase was observed in some tissues. Short-term fasting led to a decline in glycolipids in tissues such as brain (P<0.05), accessory respiratory organ (P<0.001), pectoral and lateral line muscle. Liver and kidney (P<0.002) reported an increase. Long term starvation also resulted in a decline in tissues such as liver (P<0.001), kidney (P<0.001), brain, and accessory respiratory organ. Muscle tissue, that is, both the pectoral (P<0.002) and lateral line muscle (P<0.05), showed an increase in the glycolipid fraction. This selective decline in glycolipid content of certain tissues suggests a possible utilization of these lipids during starvation and the significant upsurge observed in certain tissues suggests a simultaneous synthesis occurring along the degradation, probably reducing the oxidative stress created by ROS (reactive oxygen species).